Hysteroscopic removal of intrauterine-retained suture material causing pelvic inflammatory disease - Cihan Kaya; Ismail Alay; Sukru Yildiz; Ozgur Aslan (Wolters Kluwer Medknow Publications, 2021)
Retained intrauterine objects are rare causes of persistent vaginal discharge and pelvic inflammatory disease. Hysteroscopy is a minimally invasive technique used for removing these materials. A 47-year-old female who had recurrent vaginal discharge was admitted to our emergency department with pelvic pain. Retained nonabsorbable suture material was observed during her vaginal examination. After treating with intravenous antibiotics, operative hysteroscopy was performed, and the material was removed from the lower segment of the uterus.